Investigating the Biophysical Properties of Directional Freezing and its Application to Nondomestic Species - Gillis, James D. (2022)
The Indonesian Global Species Management Program (GSMP) is tasked with developing genetically healthy global populations of banteng, lowland anoa, and babirusa. The cryopreservation and storage of spermatozoa in biobanks could theoretically aid in conservation efforts whereby, the systematic collection and cryopreservation of spermatozoa from present day metapopulations could permit the long-term storage and movement of valuable genes through the application of assisted reproductive technologies. In recent years, there have been several advances in sperm cryopreservation technologies that significantly improve the post-thaw survival of spermatozoa. Two of these methods include the treatment of spermatozoa with cholesterol-loaded cyclodextrins (CLC) and the use of a multithermal gradient to directionally freeze spermatozoa. As these techniques are highly translatable across taxa, the combined use of these techniques may increase the amount of viable genetic material for biobanking spermatozoa from the Indonesian GSMP target species. With the domestic boar as a model, the aims of this dissertation were to investigate the effects of pre-treatment of spermatozoa with CLC, at different glycerol concentrations, using direction and conventional freezing methods to improve the post-thaw survival of spermatozoa. In addition, studies were conducted to investigate what aspects of directional freezing may improve the post-thaw survival of sperm. Finally, semen was collected and characterised from Indonesian GSMP target species to provide data that can inform future sperm cryopreservation and biobanking research. Split sample boar ejaculates were used in a factorial design to investigate the effect of CLC (0.0 or 1.25 mg/ml), glycerol concentration (1.5, 3.0, or 6.0%; v:v), and freezing method (directional freezing at interface velocities of 0.2, 0.5, 1.0, 1.5, 3.0 mm/sec or conventional cryopreservation) on sperm plasma membrane and acrosome integrity post-thaw. The percentage of sperm with both intact plasma membrane and acrosomes post-thaw was quantified by flow cytometry, using the fluorescent probes Syto17, propidium iodide, and fluorescein-conjugated Arachis hypogeal (peanut) agglutinin. At 0 h post-thaw there were no differences (p>0.05) between CLC treated and untreated sperm. A glycerol concentration of 3% produced a higher (p<0.05) percentage of sperm with both intact plasma membrane and acrosomes post-thaw and 1.5%. There were no differences (p>0.05) between conventional and the directional freezing method that produced the highest percentage of sperm with both intact plasma membranes and acrosomes. These findings suggest that while directional freezing may be an acceptable method to cryopreserve domestic boar sperm, it also confers no additional benefit compared to conventional freezing in 0.5 ml straws. To investigate the effect of ice morphology on the post-thaw survival of sperm, samples were directionally frozen using interface velocities which the literature previously identified as optimal (1.0 and 1.5 mm/sec) and suboptimal (0.2, 0.5, and 3.0 mm/sec), as well as using conventional cryopreservation methods. A combination of cryo-scanning electron microscopy and Fiji (ImageJ) Shape Descriptors (area, perimeter, aspect ratio, and roundness) were used to analyse differences in ice morphology between treatment groups. Optimal directional freezing interface velocities (1.0 and 1.5 mm/sec) resulted in different (p<0.05) ice morphologies than conventional cryopreservation methods. However, the optimal directional freezing protocols produced similar (p>0.05) ice morphologies to slower suboptimal directional freezing interface velocities (0.2 and 0.5 mm/sec) but were different (p<0.05) to faster suboptimal interface velocities (3.0 mm/sec). These findings suggest that ice morphology may be contributing to the post-thaw survival of directionally cryopreserved sperm, but cooling rate (which varies with interface velocity) is potentially limiting the conferred benefit of ice morphology on the post-thaw survival of sperm. Finally, semen was collected via electroejaculation and characterised (Mean ± SEM; volume, total sperm count, total motility (%), status (scale of 0 – 5; 0 = no forward progression, 5 = rapid and straight forward progression), and morphologically normal sperm) for banteng (n=14; 11.93 ± 2.35 ml, 2,702 ± 764 × 106 sperm, 72.7 ± 4.3%, 3.3 ± 0.1, 87.9 ± 3.0%), lowland anoa (n=18; 0.416 ± 0.104 ml, 273 ± 95 × 106 sperm, 45.6 ± 5.3%, 2.8 ± 0.2, 64.8 ± 7.4%) and a preliminary collection on a single babirusa (5.13 ml, 2,768 × 106 sperm, 65%, 3, 96%). This study provides the first detailed analysis of the ejaculates from the GSMP target species; banteng, lowland anoa, and babirusa in North America. With the domestic boar as a model, the researcher has determined that directional freezing in 0.5 ml straws does not produce significantly higher survival parameters than conventional cryopreservation methods. Ice morphologies of directionally frozen samples were not associated with the post-thaw survival of directionally frozen sperm in 0.5 ml straws. As a result, future research into optimal sperm cryopreservation methods for GSMP target species is warranted.